(3Mb GddLhA ai VhA bhGYO GdbGfhf GdOhdi eY GdJWHjb Ydi hVY GddGLFjf GdadSWjfjjf HYO GJaGbGJ GhSdh (B/ s - (3GMeO efUhQ GSeGYjds; (3MeO GHh GdhaG eMeO s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQIfs, 2006)
(3JTcd bVjI GddGLFjf GdadSWjfjjf (B: (3HGdeYfi GdObjb (B: (3GSGS GdbVjI GdadSWjfjI h GdfhGI GdUdHI ddghjI GdhWfjI GdadSWjfjI (B: (3dGfgG djSJ edaG KGfhjG ef GdedaGJ GdYOjOI hGdeJTYHI ddbVjI GdadSWjfjI (B: (3hdG jecf HGi MGd ef GdGMhGd GdfXQ GdjgG ef MjK gi fJjLI YGQVI Gh eDSaI (B: (3ef fJGFL GdUQGY ai GdTQb GdGhSWceG Gfg jJYPQ fLGM GdYedjI GdSdejI ai GdefWbI ef ZjQ ebGQHI bVjI GddGLFjf ebGQHI SjGSjI ai GdebGe GdGhddPdc (B: (3Jbhe gPg GdOQGSI Ydi GdHMK aj (B: (3GdGKGQ GdJi NdaJgG YedjI GhSdhYdi bVjI GddGLFjf GdadSWjfjjf (B: (3dGfg ef GdeHjf Gf GhSdh (B: (3bO GMOKJ eG jTHg GdUOeI ai GdghjI GdadSWjfjI (B: (3Gh HeYfi GOb GfgG GONdJ GdhWfjI GdadSWjfjI dGhd eQI efP JTcdgG HYO GdfcHI (B: (3ai eGRb GdMQL GdLGQMaGdi GdJQGLY GdeQjY ai GdGhVGY GdeYjTjI ddGLFjf GdadSWjfjjf (B: (3hGdi JRGjO GdJVjjb GdGOGQj (B: (3h GdbGfhfi Ydjge ef bHd GdYOjO ef GdOhd GdYQHjI (B: (3ceG gh GdMGd aOi dHfGf hdjHjG hOhd GdNdjL hZjQgG (B: (3aGf YedjI GhSdhGONdJ GQJHGcG TOjOG ai Uaha GddGLFjf GdadSWjfjjf HTcd NGUhJHMK GjVG ai JfGhd HYV GdMdhd ddNQhL ef GdeGRb GdJi JYGfjg bVjI GddGLFjfhPdc ef NdGd GecGfjI GYGOI JaSjQ bhGYO GdbGfhf GdOhdi ddGLFjf MJi jecf JWHjbgG Ydi GddGLFjf GdadSWjfjjf (B: (3hJOYje eQcRge GdbGfhfi GdPi GKQJ Ydjg YedjI GhSdh HTcd cHjQ (B: (3MJi GUHMhG ef ZjQ JeKjd jYHQ Yf eWGdHge GdNGUIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi, (B2006s
(3HHdjhLQGajG(B: (3UaMGJ (B193-206s
Keywords: (3GdbGfhf GdOhdjs; (3GdhKGFb GdOhdjIs; (3MeGjI GddGLFjfs; (3GdJShjI GdSjGSjIs; (3GdGee GdeJMOIs; (3GdHQhJhchd GdOhdjs; (3GdeahV GdSGejs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs